Missed opportunity for tuberculosis screening among patients presenting at two health centres in Manafwa district, Uganda - Titus Wamulima; John P.M. Masaba; David Musoke; David Mukunya; Joseph K.B. Matovu (Journal of Public Health in Africa, 2023)
Background: Missed Tuberculosis (TB) screening opportunities are key drivers of continued tuberculosis transmission. Objective: To determine the proportion of and factors associated with missing TB screening amongst patients who attended two health centres in the Manafwa district to inform future TB prevention and control efforts in Uganda. Methods: A facility-based, cross-sectional study was conducted at two public health centres offering comprehensive TB services in Manafwa district, Uganda, among patients (≥ 18 years) who presented with at least one symptom suggestive of TB. Using exit interviews, data on demographics and TB symptoms were collected using an electronic structured questionnaire. A logistic regression model was performed to determine the factors associated with missed opportunities for TB symptom screening. Results: Of the 125 patients enrolled in the study, the majority 76.0%, (n=70) of patients presented with cough for 2 weeks or more (cough of any duration for HIV positive patients) and a big proportion, 68% (n=85) of patients missed the opportunity to be screened for TB. Having a; post-primary education level (Adjusted Odds Ratio [AOR] =5.9; 95% Confidence Interval [95% CI] = 1.3, 27.1) and attending Bubulo HCIV (AOR= 0.01; 95% CI: 0.01, 0.2) were significantly associated with having a missed opportunity for TB screening. Conclusion: Slightly more than two-thirds of the patients who presented to the study health facilities with symptoms suggestive of TB missed the opportunity to be screened for TB. We suggest a need for a multifaceted intervention to improve TB screening, particularly among better-educated TB patients.